Analysis of Biological Assets in Agriculture - KANABEKOVA, Alida; ANDYBAYEVA, Gulsagat; TULEGENOVA, Roza; AIMAGAMBETOVA, Aida (Journal of Environmental Management and Tourism, 2021)
Despite the contribution of scientists to the development of the theory and practice of accounting in agricultural organizations on accounting and valuation of biological assets, it is not fully disclosed, which is associated with insufficient theoretical and methodological development of the problems of financial, tax and management accounting of biological assets and their assessment at fair value. The author determined the predicted values of the development of biological assets in agriculture in 2021 with the help of gross output, provided that the observed trend in the development of the factors included in the model-based correlation-regression analysis is maintained. Conclusions and recommendations for further accounting of biological assets in agriculture of the Republic of Kazakhstan are substantiated.